Trithioorthoester Exchange and Metathesis: New Tools for Dynamic Covalent Chemistry - Bothe, Michael (2019)
To expand the toolbox of dynamic covalent and systems chemistry, we investigated the acid-catalyzed exchange reaction of trithioorthoesters with thiols. We found that trithioorthoester exchange occurs readily in various solvents in the presence of stoichiometric amounts of strong Bronsted acids or catalytic amounts of certain Lewis acids. The scope of the exchange reaction was explored with various substrates, and conditions were identified that permit clean metathesis reactions between two different trithioorthoesters. One distinct advantage of S, S, S-orthoester exchange over O, O, O-orthoester exchange is that the exchange reaction can kinetically outcompete hydrolysis, thereby making the process less sensitive to residual moisture. We expect that the relatively high stability of the products might be beneficial in future supramolecular receptors or porous materials.